Developments and Applications of Calcium Phosphate Bone Cements - Liu, Changsheng; He, Hongyan (Springer Series in Biomaterials Science and Engineering,, 2018)
This book presents a state-of-the-art review of the latest advances in developing calcium- phosphate bone cements and their applications. It covers the synthesis methods, characterization approaches, material modification and novel binders, as well as the fabrication technologies of calcium-phosphate-based biomaterials in regenerative medicine and their clinical applications. It also highlights methodologies for fabricating scaffolds, biofunctional surfaces/interfaces and subsequently modulating the host response to implantable/injectable materials, and integrates a series of discussions and insights into calcium-phosphate cements and constructs in bone regenerative medicine. As such, the book not only covers the fundamentals but also opens new avenues for meeting future challenges in research and clinical applications. .